Synthesis and characterization of alkyl, propoxy, ethoxy-based frothers. (September 2016) - Zhang, Wei; Tan, Yue Hua; Finch, James A.
Highlights: Polyglycol frothers based on both PO and EO. Number of C(n), PO(m), EO(l) and PO/EO position studied. Increasing number decreases D32 : m > n > l. C3 [PO]3 [EO]2 has more effect than C3 [EO]2 [PO]3. Abstract: In this paper we describe the synthesis and characterization of a homologous series of linear polyglycol-based frothers comprising alkyl, propoxy (propylene oxide, PO), and ethoxy (ethylene oxide, EO) groups. The identities were confirmed by proton nuclear magnetic resonance spectroscopy and total organic carbon analysis. Characterization used three parameters, bubble size, gas holdup and water overflow rate, measured in a bubble column. The results indicate that increasing number of PO groups led to significant decrease in bubble size, and increase in gas holdup and water overflow rate. Increasing the alkyl chain length, gave similar but less pronounced trends; the least effect was increasing the number of EO groups. Changing the relative position of the PO and EO group had a significant effect on all three parameters. To account for the effect of PO/EO position, a mechanism based on effect of structure on molecule packing at the air/water interface is proposed.